FORMULATION AND ASSESSMENT OF HERBAL EMULGELS IN THE MANAGEMENT OF ACNE: IN VITRO AND IN VIVO INVESTIGATIONS - NEELA, SWAPNA; AJITHA, MAKULA; KUCHANA, VIJAYA (International Journal of Applied Pharmaceutics, 2024)
Objective: The main objective of the current research was to prepare herbal emulgel and analyze the effect of herbal formulation in the treatment of acne. Methods: The plants Tabernaemontana coronaria and Thunbergia alata were selected for the study because of folklore for their medicinal values. The T. coronaria and T. alata test extracts were prepared by soxhlet extraction procedure and subjected to physico-chemical evaluation. The formulated herbal emulgels prepared by dispersion technique were investigated for anti-acne properties by in vitro and in vivo methods. The prepared emulgel formulations were assessed for parameters like viscosity, spreadability, pH, content uniformity, stickiness, zeta potential, particle size, surface morphology, and in vitro diffusion studies. Results: The physico-chemical evaluation of herbal gel revealed that emulgel appeared light green in colour, opaque, and odourless with smooth texture. The emulgels of both the test extracts showed no stickiness, and revealed pH ranging from 5.467±0.13 to 5.889±0.1. When the shear rate was increased, there was a decrease in the viscosity of the test emulgels, with good extrudability. The content uniformity of F5 emulgel for T. coronaria and T. alatawas 99%, and spreadibilty was more with F7 formulation of T. coronaria and F6 formulation of T. alata, respectively. In the stability testing studies, amongst all the formulations prepared, F5 was found to be stable upon storage for six months. In vitro studies, F5 formulation of both the test extracts had a remarkable zone of inhibition; whereas F5 formulation treated histopathological sections in in vivo investigation displayed a decline in the overall damage induced by Propionibacterium acnes. The results showed no statistical significant difference for measurement of zone of inhibition and histopthological studies between the test formulations and standard drug. Conclusion: The study concludes that both herbal formulations were promising agents for the treatment of acne vulgaris.